Pengembangan Kurikulum Berorientasi pada Karakter Membangun Kepribadian Siswa - Wahidin; Nurazizah; Syaeful Anwar; Nurdin Rohendi, Muh; Ika Kartika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The curriculum is an important instrument of a country's education system. It is the main foundation in determining educational objectives, subject matter content, teaching methods, and evaluation systems. In the world of education, the role of the curriculum is very important, it can even be said that the curriculum plays a key role in the education system. Because the curriculum is closely related to determining the direction, content, and educational process. In addition to curriculum development, it is necessary to pay attention to the character building of students and this has a very important role. Along with technological advances and information flows, as well as the continuing process of globalization in various aspects of public life, it will affect the mindset and pattern of action of the wider community. To fortify and minimize things that have bad consequences, an education is needed that can improve morals and build human character itself. The methodology used in this research is a qualitative method, which is a type of literature review by reviewing books and journals that have been publishedHistory of curriculum development in Indonesia has undergone ten changes that occur due to changes in social and political conditions. In Indonesian Dictionary, the word character is defined as character, psychological qualities, morals or ethics that distinguish a person from others, and disposition. Character person means a person who has personality, behavior, character, character, or character. Character education is a conscious and planned effort that aims to internalize moral values, morals so that they are manifested in the implementation of good attitudes and behaviors.The implementation of character education involves aspects of knowledge theory (cognitive), feelings (feeling), and action (action). The purpose of education should be directed at developing all the potential that a person has towards his perfect development, namely physical, intellectual and ethical development. Success in building student character will automatically help the success of building the nation's character. Therefore, the progress of a nation will also depend on the character and intelligence capabilities of its citizens